An association study of polymorphisms in the P2RX7 gene in an Iranian population with the risk of type 2 diabetes mellitus - Homa Noori; Majid Rajabian; Mahdi Majidpour; Mahboobeh Sabeti Akbar-Abad; Ramin Saravani (Egyptian Journal of Medical Human Genetics)
Abstract Objective Type 2 diabetes mellitus (T2DM) showed a broad etiology that both environmental and genetic factors play a role in its predisposition. Purinergic receptors have been hypothesized to be included in the pathogenicity of T2DM. The current study evaluated the association of two variants through the purinergic receptor P2X7 (P2RX7) gene with the incidence of T2DM in the population of Iran. Materials and methods We study includes 600 subjects as case and healthy groups clinically diagnosed with T2DM by clinicians referred to the diabetic clinic of Bu-Ali Hospital, Zahedan. DNA extraction followed by tetra amplification refractory mutation system polymerase chain reaction (Tetra ARMS-PCR) as a genotyping method. Results Regarding rs1718119, the codominant heterozygous (TC vs. TT), Dominant (TC + CC vs. TT), Over dominant (TC vs. TT + CC) and Allelic (C vs. T) inheritance models increased T2DM risk by 2.81, 2.94, 1.62, and 2.20 folds, respectively. Similarly, in the variant rs17525809 in the same models, the analysis showed that increased T2DM risk by 3.31, 2.56, 3.25, and 2.02 folds, respectively. Based on haplotype analysis, Crs1718119Crs17525809, Crs1718119Trs17525809 and Trs1718119Crs17525809 haplotypes significantly enhance T2DM risk by 3.97, 1.36 and 1.82 folds, respectively. Furthermore, the interaction analysis indicated that TCrs1718119/TCrs17525809, TCrs1718119/TTrs17525809 and TTrs1718119/TCrs17525809 genotype combinations strongly correlated with high T2DM risks by 7.80, 1.75 and 2.92 folds, respectively. Conclusions Our findings showed that both rs1718119T > C and rs17525809T > C increased the risk of T2DM in the Iranian population. Graphical abstract